Analisis Strategi Pemasaran Pembiayaan Murabahah Pada Produk Cicil Emas Dalam Meningkatkan Jumlah Nasabah Pada Bank Syariah Indonesia (BSI) KCP. Medan Krakatau - Ravita, Ravita (STAI Denpasar Bali, 2024)
The growth of the Sharia Banking industry in Indonesia continues to show a positive trend in line with increasing public awareness of finance and financial solutions that comply with sharia principles. One product that is attracting attention in this context is murabahah financing, especially in the form of Gold Installments, as a marketing strategy that is expected to not only retain customers, but also increase the number of customers significantly. The aim of this research is to determine the marketing strategy for murabahah financing on gold installment products in increasing the number of customers at Bank Syariah Indonesia KCP. Krakatoa Field. This article will conduct an in-depth analysis of the marketing strategy for Bank Syariah Indonesia's gold installment products, identify the factors that contributed to success, and detail the impact on increasing the number of customers at the Sharia Bank. This research uses qualitative research while the data collection methods used are interviews, observation and literature study. The results of this research show that in increasing the number of customers of Bank Syariah Indonesia, KCP Medan Krakatau implemented a strategy that focused on segmentation, targeting, positioning and marketing mix. Among these strategies, the main focus is on publicity methods included in the marketing mix. The publicity method is the most effective means of building a brand image, which in turn can increase the growth of gold installment customers. Other supporting factors are also influential, such as Bank Syariah Indonesia carrying out appropriate market segmentation by focusing marketing efforts on target groups who have a need for gold financing, such as the adult age group with a fixed income, while in terms of positioning strategy, Bank Syariah Indonesia KCP Medan Krakatau positions itself as a safe and beneficial business partner.